La ocupación del espacio geográfico y el desarrollo de los sistemas de producción agrícola en el distrito de El General, Pérez Zeledón. Costa Rica (1850-1950) - Durán Barrantes, Norman Dimas (2005)
This work addresses the development process of the agricultural front in El General, Pérez Zeledón, that took place during the second half of the nineteenth century and the first half of the twentieth century. Here, spatial characteristics are analyzed, as well as the components of the production units and systems in these territories and the transformations they experienced. Along with a revaluation of the agricultural complexity present in the region during this period, this article highlights the role of governmental policies pertaining to the settlement of the southern region and its connection with the national economic framework